Positional training demands in the English Premier League and English Championship. A longitudinal study across consecutive seasons - Morgans, R.; Ceylan, I. H.; Radnor, J.; Ryan, B.; King, M.; Zmijewski, P.; Oliveira, R. (Biology of Sport, 2025)
The aims of this study were to: compare training loads between the English Premier League (EPL) and English Championship League (ECL) and examine differences between playing positions. Forty-six 1st team players from the same club participated in the study. GPS metrics were obtained during all EPL and ECL training sessions across four consecutive seasons, 2019-20 to 2022-23. The study team was promoted from the ECL at the end of season 2020-21. There was a significant interaction effect between position and league for all GPS metrics (p < 0.001; ?2 = 0.001-0.003), except for relative high-speed running (HSR) distance, sprint distance, and sprint efforts (p > 0.05). A significant main effect for league for all GPS metrics (p < 0.001; ?2 = 0.001-0.009) was found, with EPL training sessions resulting in greater total distance per minute, HSR distance per minute, high metabolic load distance (HMLD) per minute, number of HML efforts, accelerations, and decelerations per minute compared to training in the ECL (p < 0.001; d = 0.061-0.224). For position, a significant main effect for all GPS metrics (p < 0.001; ?2 = 0.001-0.005) was observed. Centre midfielders covered more distance per minute than all other positions (p < 0.001, d = 0.040-0.167). In conclusion, higher training values in the EPL were evident, except for centre forwards, providing some guidance on the differing positional physical demands that may support coaches and practitioners to design position-specific drills incorporating physical and technical/tactical strategies.